Effectiveness and Institutional Conditions in Social Forestry Program: Case Study of Forest Village Community Institution (LMDH) Sumber Makmur, Forest Management Unit (KPH) Malang - Ramadhan, Ramli; Syah, Deni Firman; Waskhito, Nugroho Tri (Jurnal Sylva Lestari, 2022)
Changes in the Social Forestry or Perhutanan Sosial (PS) scheme have been made by the Ministry of Environment and Forestry of the Republic of Indonesia, particularly in the state-owned forestry enterprise (Perhutani) working area. A forestry partnership is one of the schemes being developed to replace the previous scheme, Community Forest Management (PHBM). However, increased PS area permits are not always accompanied by increased farmer trust and understanding of the program. This study aimed to determine the institution's effectiveness and institutional condition in the era of PS policy, which is currently a government priority program. One of the community groups granted a management permit is the Forest Village Community Institution (LMDH) Sumber Makmur, located in the Forest Management Unit (KPH) Malang. This study was conducted from December 2020 to March 2021 using a qualitative descriptive method as in-depth interviews and questionnaires with assessment indicators. Respondents were chosen randomly from the entire population using the Slovin formula. The results showed that the institutional effectiveness of LMDH Sumber Makmur still tended to decrease. The confidence level of farmers in the PS program was only around 28.9%, and the level of understanding was 26.7%. The results also showed a low percentage value of farmer participation, external support, the availability of facilities, and gender perspective. Consequently, the government needs to monitor institutions and community groups running PS programs to see institutional developments in each location. Institutional development is essential as an entrance for people to manage forests independently. Keywords: Forest Village Community Institution, institutional conditions, institutional effectiveness, social forestry